(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This article is written in the context of two European cultures from two countries with different histories, both universities collaborating in the field of digital arts. The aim of the study is to provide clear methods for the use of digital tools in higher education for students of architecture and visual arts. To achieve this objective, ten tasks have been set and the results are presented in this paper. The methods used in the study include observation, photo-fixation, Prototyping interior design with artificial intelligence, literature studies, modelling, surveys, and interpretation of their results through graph-analytical methods. The authors present the positive and critical aspects of education: artificial intelligence is powerful and fast at processing huge amounts of data that humans should be able to process over an incomparably longer period, but it is poor at judging people and art. AI accurately processes billions of websites and resources to offer the best results for our search queries, and it has beaten the reigning champions in many intellectual games. But based on their own and others' research, the authors show how inaccurate AI is, for example in predicting whether individuals who have previously used AI in their artwork might achieve better results than if they had produced their own work using their own talent and personal experience. AI is no better than a simple guess, and yet AI is being used to determine people's futures. One of the experts discussed by the authors is Zweig, who introduces us to the basics of AI and provides a toolkit for designing AI systems. Finally, all the respondents explore the ethics of AI and how we can shape the process, prepared us for the biggest question about AI: where we should use it - and where we should not with a particular focus on the quality of education, developing young people's creative abilities, fostering critical thinking and responsible decision-making.